The Protective Potential Role of ACE2 against COVID-19 - Fereshteh Golab; Gelareh Vahabzadeh; Leila SadeghRoudbari; Arefeh Shirazi; Robabeh Shabani; Sara Tanbakooei; Lida Kooshesh (Advances in Virology, 2023)
Due to the coronavirus disease 2019 (COVID-19), researchers all over the world have tried to find an appropriate therapeutic approach for the disease. The angiotensin-converting enzyme 2 (ACE2) has been shown as a necessary receptor to cell fusion, which is involved in infection due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is commonly crucial for all organs and systems. When ACE2 is downregulated via the SARS-CoV-2 spike protein, it results in the angiotensin II (Ang II)/angiotensin type 1 receptor axis overactivation. Ang II has harmful effects, which can be evidenced by dysfunctions in many organs experienced by COVID-19 patients. ACE2 is the SARS-CoV-2 receptor and has an extensive distribution; thus, some COVID-19 cases experience several symptoms and complications. We suggest strategy for the potential protective effect of ACE2 to the viral infection. The current review will provide data to develop new approaches for preventing and controlling the COVID-19 outbreak.